Synthesis and characterization of photocatalytic polyurethane and poly(methyl methacrylate) microcapsules for the controlled release of methotrexate - Al-Nemrawi, Nusaiba K. (2018)
The aim of this work is to prepare ultraviolet (UV) triggered controlled release of compounds from microcapsule systems (MCs). Polyurethane (PU) and poly(methyl methacrylate) (PMMA) microcapsules were studied with/without chemical functionalization using photocatalytic TiO2 nanoparticles (NPs) on their surface. Once TiO2 nanoparticles are illuminated with UV light (λ = 370 nm), they initiate the rupture of the polymeric bonds of the microcapsule and subsequently initiate the encapsulated compound release, methotrexate (MTX) or rhodamine (Rh), in the present work. The size, polydispersity, charge, and yield of all MCs were measured, being the methotrexate drug release for all systems determined and compared with and without functionalization with TiO2 NPs, under dark, visible light and UV illumination in vitro. Finally, the Rh release was characterized using fluorescence microscopy. The TiO2 NPs size is around 10 nm, as determined by X-ray diffraction experiments. The PU MCs average size is around 60 µm, its electric charge +3.11 mV and yield around 85%. As for the PMMA MCs, the average size is around 280 µm, its electric charge −7.2 mV and yield around 25% and 30% for both MTX and Rh, respectively. In general, adding TiO2 NPs or the encapsulated products to the MCs does not affect the size but functionalization with TiO2 NPs lowers the electric charge. Microcapsules functionalized with TiO2 nanoparticles and irradiated with UV light presented the highest release of MTX and Rh. All other samples showed lower drug release levels when studied under the same conditions.